Median thoracic expansion combined with Nuss procedure for asphyxiating thoracic dystrophy - Wenlin Wang; Weiguang Long; Yang Liu; Bin Cai (Elsevier, 2022)
Asphyxiating thoracic dystrophy is an extremely rare and complex thoracic deformity, and its operation is challenging. In the past, several kinds of operations have been reported, but they all have disadvantages. We designed a new surgical technique that combines median thoracic expansion with Nuss procedure, and we applied this technique to a 1-year-old patient with asphyxiating thoracic dystrophy and achieved satisfactory results.